Carnitine is associated with fatigue following chemoradiotherapy for head and neck cancer. (August 2015) - Endo, Kazuhira; Tsuji, Akira; Kondo, Satoru; Wakisaka, Naohiro; Murono, Shigeyuki; Yoshizaki, Tomokazu
Abstract Conclusion: Longitudinal assessments of carnitine and fatigue in patients with head and neck squamous cell carcinoma suggest that cisplatin damages the carnitine system in patients undergoing chemoradiotherapy and that carnitine deficiency increases fatigue. Objectives: The purpose of this study was to monitor carnitine levels and fatigue in patients who received cisplatin-based CRT and, for comparison, in patients treated by surgery alone. Methods: To investigate the level of carnitine, mice were administered cisplatin. Next, a prospective analysis was performed to compare plasma carnitine levels before and after cisplatin-based chemoradiotherapy and to assess the relationship between carnitine levels and fatigue. Results: The plasma levels of total carnitine (TC), free carnitine (FC), and fatty acylcarnitine (AC) were significantly lower in mice receiving cisplatin compared with control mice. Mean total carnitine and free carnitine levels were significantly lower 2 weeks after chemoradiotherapy (total carnitine: Mean = 45.6, SD = 16.5, p = 0.01; free carnitine: Mean = 37.8, SD = 12.7, p = 0.02) than before chemoradiotherapy (total carnitine: Mean = 57.7, SD = 12.2; free carnitine: Mean = 48.1, SD = 11.6). There was a significant inverse correlation between carnitine levels and fatigue after chemoradiotherapy.